ANALYSIS OF THE RELATIONSHIP OF SOCIAL CAPITAL WITH POVERTY OF FISHERMEN IN BONTO BAHARI VILLAGE, BONTOA DISTRICT, MAROS DISTRICT - Helah Hesegem; Abdul Rahim, Syamsu Alam, Sri Astuty (CV. Adiba Aisha Amira, 2024)
This research aims to determine the relationship between social capital and the poverty of fishermen in Bonto Bahari, Bontoa District, Maros Regency. The type of research used is quantitative research. The types of data utilized are primary data and secondary data. The data analysis technique used in this research is Structural Equation Modelling. (SEM). The results of this research indicate that the social capital in terms of community trust is quite good in improving the welfare of poor families. The social capital of social networks in the research area is relatively good for enhancing the welfare of poor families, and the social capital of social norms in the research area is also relatively good for improving the welfare of poor families.